Hubbard family papers - Hubbard, Gardiner G. (Gardiner Greene), 1822-1897.; Hubbard, Gertrude Mercer McCurdy, 1827-1909.; Hubbard, Samuel, 1785-1847.; McCurdy, Robert Henry, 1800-1880.
Chiefly correspondence supplemented by diaries, speeches, writings, notes, printed matter, drawings, and other papers of members of the Hubbard family and allied Bell, Greene, and McCurdy families. Primarily the papers of Gardiner G. Hubbard; his wife, Gertrude Mercer McCurdy Hubbard; his father, Samuel Hubbard; and his father-in-law, Robert Henry McCurdy. Documents Gardiner G. Hubbard's interest in the education of the deaf; the Caledonia Mine, Glace Bay, N.S.; the Moxee Company, a ranch near North Yakima, Wash.; and the Bell telephone system in Europe. Also includes papers relating to Robert McCurdy's activities during the Civil War, especially with the Union Defence Committee of the City of New York.
Family correspondents include Alexander Graham Bell, Mabel Gardiner Hubbard Bell, Edgcumb H. Blatchford, Elizabeth Greene Hubbard Buck, Theodore Frelinghuysen, Elizabeth Hubbard Greene, Gardiner Greene, Daniel Hubbard, Mary Anne Greene Hubbard, Mary Greene Hubbard, and Gertrude Mercer Lee McCurdy. Other correspondents include Gorham D. Abbott, William F. Channing, Joseph H. Converse, Henry L. Dawes, L. De Groof, Edward Everett Hale, Sr., Russell Hinman, Eben Norton Horsford, William Ker, S.P. Langley, D.E. Lesh, Nathan Lord, William Orton, Harriet Burbank Rogers, Cornelius Van Schaack Roosevelt, Adam Scott, Samuel Storrow, and Ida M. Tarbell.
Library of Congress Prints and Photographs Division.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Abbott, Gorham D., -- 1807-1874 -- Correspondence; Bell, Alexander Graham, -- 1847-1922 -- Correspondence; Bell, Mabel Gardiner Hubbard, -- 1857-1923 -- Correspondence; Blatchford, Edgcumb H. -- 1811-1853 -- Correspondence; Buck, Elizabeth Greene Hubbard, -- 1817-1890 -- Correspondence; Channing, William F. -- 1820-1901 -- Correspondence; Converse, Joseph H. -- Correspondence; Dawes, Henry L. -- 1816-1903 -- Correspondence; De Groof, L. -- Correspondence; Frelinghuysen, Theodore, -- 1787-1862 -- Correspondence; Greene, Elizabeth Hubbard, -- 1760-1797 -- Correspondence; Greene, Gardiner, -- 1753-1832 -- Correspondence; Hale, Edward Everett, -- Sr., -- 1822-1909 -- Correspondence; Hinman, Russell, -- 1853-1912 -- Correspondence; Horsford, Eben Norton, -- 1818-1893 -- Correspondence; Hubbard, Daniel, -- 1736-1765 -- Correspondence; Hubbard, Mary Anne Greene, -- 1790-1827 -- Correspondence; Hubbard, Mary Greene, -- 1734-1808 -- Correspondence; Ker, William, -- 1852-1925 -- Correspondence; Langley, S. P. -- 1834-1906 -- Correspondence; Lesh, D. E. -- 1853-1924 -- Correspondence; Lord, Nathan, -- 1792-1870 -- Correspondence; McCurdy, Gertrude Mercer Lee, -- 1810-1876 -- Correspondence; Orton, William, -- 1826-1878 -- Correspondence; Rogers, Harriet Burbank, -- 1834-1919 -- Correspondence; Roosevelt, Cornelius Van Schaack, -- 1794-1871 -- Correspondence; Scott, Adam, -- approximately 1842- -- Correspondence; Storrow, Samuel -- Correspondence; Tarbell, Ida M. -- 1857-1944 -- Correspondence; Bell family; Green family; Hubbard family; McCurdy family; United States. -- Army -- Recruiting, enlistment, etc; United States. -- Army -- Supplies and stores; Bell Telephone Company; Caledonia Mine (Glace Bay, N.S.); Moxee Company; Union Defence Committee of the City of New York; Deaf -- Education; Mines and mineral resources -- Nova Scotia -- Glace Bay; Ranches -- Washington (State); Telephone -- Europe; Telephone companies -- Europe; New York (N.Y.) -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Greene family